Association between vitamin D status and physical performance in COVID-19 survivors: Results from the Gemelli against COVID-19 post-acute care project. (July 2022) - Galluzzo, Vincenzo; Ciciarello, Francesca; Tosato, Matteo; Zazzara, Maria Beatrice; Pais, Cristina; Savera, Giulia; Calvani, Riccardo; Picca, Anna; Marzetti, Emanuele; Landi, Francesco; ,
Abstract: Aim: To determine the prevalence and associated factors of vitamin D deficiency in COVID-19 survivors and the relationship between vitamin D status and physical performance. Methods: Vitamin D status was assessed in a sample of patients who had recovered from COVID-19 and were admitted to a post-acute outpatient service at the Fondazione Policlinico Universitario Agostino Gemelli IRCCS (Rome, Italy). Participants were offered comprehensive medical assessment, including physical performance and muscle strength tests. Self-rated health was assessed. Vitamin D deficiency was defined as a serum concentration of 25-OH vitamin D < 20 ng/mL. Results: Mean age of 681 participants was 53.4 ± 15.2 years and 49% were women. Vitamin D deficiency was detected in 35.6% of the whole study population, and in 40.2% of those 65 and older. Vitamin D deficiency was associated with diabetes, higher body mass index, and COVID-19 severity, and showed a seasonal pattern with a peak in autumn/winter. Participants with vitamin D deficiency performed poorer on the six-minute walking test, with the lowest performance observed in those 65 and older. No significant associations with any other parameters were found. Conclusion: Our findings indicate that vitamin D deficiency is frequent in COVID-19 survivors, especially in older adults. Low vitamin D levels are associated with poor physical performance, in particular in old age. Highlights: Vitamin D deficiency is common in COVID-19 survivors, especially in old men. Vitamin D deficiency is associated with cardiometabolic risk factors and COVID-19 severity. Vitamin D deficiency is associated with poor physical performance.